Verification of the therapeutic process in cleft patients - Bautzer,Ana Paula Doi (2014)
PURPOSE: This study was conducted to verify the origin of a longer or even failed therapeutic process in patients with cleft lip and palate as to its difficulty. METHODS: Eighteen children undergoing therapeutic process were observed for at least 6 months and divided into two groups: presenting isolated cleft lip and palate (group I) and having been diagnosed by a Speech-Language Pathologist with reading and writing disorders, with manifestation of phonological awareness deficit (group II). Two tests were applied for the evaluation of speech and language: ABFW Language Test for Young Children (phonology) and Phonological Awareness: Instrument of Sequential Assessment (CONFIAS). RESULTS: Group I presented higher percentages in ABFW test than group II, except in the "simplification of consonant cluster" and "plosive devoicing" variables. It was also observed that, in the process of omission, group I hardly omits the vibrant consonant, as observed in group II. At the syllable level of CONFIAS, the percentages observed in group I tended to be higher than in group II, with the exception of the following tasks: "medial syllable," "production of rhyme," and "exclusion." At the phoneme level, the percentages observed in group II tended to be higher than in group I, with the exception of the following tasks: "starts with given sound," "exclusion," "synthesis," and "segmentation." No significant difference was observed between percentage distributions in groups I and II (p>0.118). CONCLUSIONS: The differences found between groups I and II, although not statistically significant, may suggest that the presence of malformation hinders speech and language acquisition and development and prolongs the therapeutic process if directive interventions are not carried out, including phonological awareness therapy.